A green and facile approach for hydrothermal synthesis of LiFePO4 using iron metal directly. (1st December 2016) - Bolloju, Satish; Rohan, Rupesh; Wu, Shao-Tzu; Yen, Ho-Xin; Dwivedi, Gopeshwar D.; Lin, Yuya A.; Lee, Jyh-Tsung
Graphical abstract: Highlights: LiFePO4 has been synthesized by a facile hydrothermal method using iron metal directly as an iron source. Theoretically iron metal delivers 100% atom economy. The LiFePO4 electrode demonstrates good electrochemical performance. Abstract: Hydrothermal LiFePO4 has been successfully synthesized using iron powder as an iron source and as an in situ reducing agent. The 100% atom economy delivered by iron metal (Fe 0 ) makes this process green and inexpensive. A plausible mechanism for the formation of hydrothermal LiFePO4 powder is also proposed. The structure of the LiFePO4 powder is well characterized by X-ray diffraction, scanning electron microscopy and transmission electron microscopy techniques. The discharge capacity of the LiFePO4 electrode is found to be 165 mAh g −1 at 0.1 C-rate, and the cycle-life performance is comparable to the conventionally synthesized LiFePO4 .